RANCANGAN SISTEM PENYEDIA AIR BEBAS MINERAL MENGGUNAKAN MEMBRAN UNTUK IRRADIATOR GAMMA 2X 250 Kci - Tri Harjanto; Ari atmoko (BATAN, 2012)
A DESIGN OF DEMINERALERALIZED WATER SUPPLY WITH MEMBRANE SYSTEM PROCESS OF GAMMA IRRADIATOR 2X250 KCI. It has been carried out gamma irradiator installation design 2 x 250 K Ci for the preservation of agricultural products, which use mineral-free water in the storage pool isotope radiation sources with volume 80 000 liter pool. To meet the waterrequirements needed design right system and meet the specified quality standards, the capacity is 1000 liters per hour, using only a minimal resin finishing, water quality is stable and is also in linewith the space available, then the selected mineral-free water treatment system with membranereverse-osmosis (RO). The principle of this process starts from raw water into the multi-media filter to filter the coarse solution, then enter the size of 0.5 micron filter catrige and then 0.1 micron contaminants like bacteria, virus, metal ions and other separated by a membrane reverse-osmosisby 99% so that the total rejection desolved solid (TDS) becomes small and almost the percent conductivity becomes too small. As controlling the conductivity of the resin used to capture the last of the ions remaining to be mineral-free water-quality standards that meet. Results design toproduce 1000 liters per hour capacity required 1600 liters of raw water per hour, 4 kW electric power, space required 3 x 3 m 2Keywords: design, demineralized water, irradiator pool, membrane, RO. RANCANGAN SISTEM PENYEDIA AIR BEBAS MINERAL MENGGUNAKAN MEMBRAN UNTUK IRRADIATOR GAMMA 2X 250 KCI. Telah dilakukan rancangan instalasi irradiator gamma 2 x 250K.Ci untuk pengawetan produk pertanian, yang menggunakan air bebas mineral pada kolampenyimpan isotop sumber radiasi dengan volume kolam 80.000 liter. Untuk memenuhi kebutuhanair tersebut diperlukan prarancangan sistem yang tepat dan memenuhi standard kualitas yangditetapkan, yaitu kapasitasnya 1000 liter/jam, menggunakan resin minimal hanya sebagai finishing,kualitas air stabil dan sesuai pula dengan ruangan yang tersedia, maka dipilih sistem pengolahanair bebas mineral dengan membran reverse-osmosis (RO). Prinsip proses ini diawali dari air bakumasuk ke multi media filter untuk menyaring larutan kasar, kemudian masuk ke filter catrigeberukuran 0,5 micron dan 0,1 micron selanjutnya kontaminan seperti bakteri, virus, ion-ion logam dan lain-lain dipisahkan oleh membran reverse-osmosis dengan rejeksi 99 % sehingga Totaldesolved solid (TDS) menjadi kecil hampir seperseratusnya dan konduktivitas menjadi kecil pula. Sebagai pengendali konduktivitas terakhir digunakan resin untuk menangkap ion-ion yang masihtersisa sehingga menjadi air bebas mineral yang memenuhi kulitas standard. Hasil prarancanganuntuk menghasilkan kapasitas 1000 liter/jam diperlukan air baku 1600 liter/jam, daya listrik 4 kW,ruangan yang diperlukan 3 x 3 m2